Advanced design techniques for RF power amplifiers - Rudiakova, Anna.; Krizhanovski, Vladimir; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Advanced Design Techniques for RF Power Amplifiers' main aim is to provide the reader with a deep analysis of theoretical aspects, modelling, and design strategies of RF high-efficiency power amplifiers. Advanced Design Techniques for RF Power Amplifiers begins with an analytical review of current state of the problem. Then it moves to the theoretical analysis of BJT class-F power amplifier near transition frequency and presents the necessary realization conditions. The next part concerns the practical verification and demonstration of the theoretical results. It is followed by the part devoted to the output networks of high-efficiency power ampifiers. The novel type of photonic band-gap structure providing improved characteristics both in the pass and stop bands is proposed. Finally, the fifth-harmonic peaking class F power amplifier design based on the above structure is presented.
to the RF Power Amplifiers Design -- Theoretical Analysis of BJT Class-F Power Amplifier -- BJT Class-F power Amplifier Design -- PBG Structure as Amplifier Output Network -- BJT Fifth-Harmonic Peaking Class F Power Amplifier.
Keywords: Engineering; Engineering design; Electrical engineering; Electronics; Microelectronics; Electronic circuits; Engineering; Communications Engineering, Networks; Circuits and Systems; Electrical Engineering; Engineering Design; Electronics and Microelectronics, Instrumentation; Electronic books